Higher CD19+CD25+ Bregs are independently associated with better graft function in renal transplant recipients - Ibrahim, Eman; Aly, Mostafa Gaafa; Opelz, Gerhard; Morath, Christian; Zeier, Martin; Süsal, Caner; Sayed, Douaa M.; Hassan, Eman; Ekpoom, Naruemol; Daniel, Volker (BMC nephrology, 2021)
The Identification of B cell subsets with regulatory functions might open the way to new therapeutic strategies in the field of transplantation, which aim to reduce the dose of immunosuppressive drugs and prolong the graft survival. CD25 was proposed as a marker of a B-cell subset with an immunosuppressive action termed Bregs. The effect of CD19 + CD25 + Bregs on graft function in renal transplant recipients has not yet been elucidated. We investigated a potential impact of CD19 + CD25 + Bregs on renal graft function as well as a possible interaction of CD19 + CD25 + Bregs with peripheral Tregs in healthy controls, end-stage kidney disease patients (ESKD), and renal transplant recipients. Moreover, we aimed to investigate the association of CD19 + CD25 + Bregs with serum IL-10, TGF-ß1, and IFN-γ in the same study groups.